2013
DOI: 10.1177/230949901302100111
|View full text |Cite
|
Sign up to set email alerts
|

Medial Arch Orthosis for Paediatric Flatfoot

Abstract: purpose. To evaluate any correlation between various foot angles and their respective American Orthopaedic Foot and Ankle Society (AOFAS) scores for pain, and the effectiveness of a medial arch orthosis. Methods. 81 children with bilateral symptomatic flatfoot were randomised into orthosis (n=55) and control (n=26) groups. The orthosis group consisted of 33 male and 22 female patients aged 36 to 204 (mean, 99) months and they were given a medial arch support. The control group consisted of 15 male and 11 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 32 publications
1
34
0
2
Order By: Relevance
“…As per NHMRC levels of evidence, three studies were rated as Level II (RCTs) [ 28 – 30 ], two studies as level III-2 (Case-controls) [ 31 , 32 ] and six studies were rated level IV (five case-series [ 33 37 ] and one single case study [ 38 ]). The main methodological concerns amongst the included studies were: lack of justification of the sample size (only one study did the power calculation [ 36 ]); lack of clear diagnostic criteria on how pes planus was diagnosed (only five studies cited their criteria for diagnosis [ 30 , 32 , 35 37 ]); lack of psychometrically robust outcome measures [OMs] (validity and reliability recorded in one study [ 35 ] and four studies reporting validity only [ 29 , 31 , 33 , 38 ]); lack of detailed descriptions regarding intervention (only six studies provided adequate description of the FOs used [ 33 38 ]); and lack of reporting of clinical significance (only two studies included the effect sizes [ 36 , 37 ]). Furthermore, the method of randomisation was not mentioned within the three RCTs and two studies failed to adequately detail the ethics approval and participants’ consent [ 9 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As per NHMRC levels of evidence, three studies were rated as Level II (RCTs) [ 28 – 30 ], two studies as level III-2 (Case-controls) [ 31 , 32 ] and six studies were rated level IV (five case-series [ 33 37 ] and one single case study [ 38 ]). The main methodological concerns amongst the included studies were: lack of justification of the sample size (only one study did the power calculation [ 36 ]); lack of clear diagnostic criteria on how pes planus was diagnosed (only five studies cited their criteria for diagnosis [ 30 , 32 , 35 37 ]); lack of psychometrically robust outcome measures [OMs] (validity and reliability recorded in one study [ 35 ] and four studies reporting validity only [ 29 , 31 , 33 , 38 ]); lack of detailed descriptions regarding intervention (only six studies provided adequate description of the FOs used [ 33 38 ]); and lack of reporting of clinical significance (only two studies included the effect sizes [ 36 , 37 ]). Furthermore, the method of randomisation was not mentioned within the three RCTs and two studies failed to adequately detail the ethics approval and participants’ consent [ 9 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A range of research designs, with participants from various countries were identified for this systematic review. The studies were conducted in Korea [ 29 , 33 35 ], India [ 28 , 30 ], Iran [ 32 , 36 , 37 ], China [ 38 ] and Poland [ 31 ], published between January 2011 and July 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…o Boks y cols. [48][49][50] . Esta reducción fue significativamente mayor en las OE y OR que en la OP, probablemente debido a los conservadores 5-6°de inversión de la OP.…”
Section: Discussionunclassified
“…Most of the studies were on the medial arch support rather than on the Blake internal foot assist. As part of a research project to develop foot orthoses to relieve symptoms, Sinha et al [8] measured pain in the forefoot, midfoot, and hindfoot of 81 children with bilateral pes planus after wearing a medial longitudinal arch support, and Robert et al [9] examined 22 subjects (6 to 57 years old) with pes planus who were wearing custom foot orthoses. They noted the changes in the lateral talocalcaneal angle during their X-ray imaging assessment of the effect of a medial longitudinal arch support on flexible pes planus.…”
Section: Introductionmentioning
confidence: 99%